Unravelling Nested Institutional Arrangements - Levesque, Mario RJ (My University, 2008)
Common pool resources (CPRs) are noted for their excludability and subtractability issues and early academic commentary stressed that due to the resources' complexity and uncertainty, management efforts were futile and a "tragedy of the commons" was the end result. Recent academic commentary has challenged this end result and has elaborated institutional design principles to sustainably manage CPRs which include the need for nested institutional arrangements (NIAs). However, little is known about how to move between the two extremes, that is, how we change public policy in a move towards and the sorts of institutional innovations that lead us to greater sustainability. This research begins to unravel nested institutional arrangements. It develops a framework for what constitutes a nested institutional arrangement and measures their effect on groundwater policy changes (frequency, type, magnitude) under different conditions of uncertainty as applied to a comparative case study between the Great Lakes Basin (high uncertainty; Ontario, New York) and the Ogallala Aquifer in the U.S. Midwest (low uncertainty; Nebraska). This dimensional mapping reveals the centrality of the nature of the linkages between governance units (especially linkage functionality), linkage complementarity and the effects of diffuse authority structures. In short, it is possible to unravel what an NIA is from the various strands in the literature and to develop linkages between NIAs and outcomes for particular situations (e.g. high vs. low uncertainty areas) in relation to common pool resources (e.g. groundwater). The results provide theoretical guidance for the study of groundwater policy changes by staking out the broad parameters of a strategy for groundwater policy change.
Keywords: common pool resources; nested institutional arrangements; groundwater policy changes; public policy; institutional innovation